Analysis of Cutting Forces with Application of the Discrete Wavelet Transform in Titanium Ti6Al4V Turning - Karolczak, Pawel (Manufacturing Technology Journal, 2023)
The paper presents the possibilities of using the wavelet transform to filter the cutting force signal. Tests were carried out by dry turning on the Ti6Al4V alloy with variable cutting parameters. Four blades with different nose geometry and coatings were used. From the recorded waveforms, the mean values of the force component Fc and the load stability coefficient were calculated. The measured force waveforms were filtered with Daubechies 4 (db4) and Daubechies 6 (db6) wavelets. From the ratio of the load stabil-ity after filtration to the load stability before filtration, the noise and disturbance values generated during the turning of the tested alloy and the force measurement were estimated. The conducted research shows how the machining conditions affect the values of force, stability, and thus also the variability of the cutting edge load when turning a titanium alloy. They also show the effectiveness of the Discrete Wave-let Transform (DWT) in separating the noise from the force signal.
Keywords: Titanium alloys; Cutting forces; Wavelet analysis; Load stability; Measurement disturbances